2010
DOI: 10.1111/j.1463-1326.2010.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline completely reverses mechanical hyperalgesia in diabetic rats through microglia-induced changes in the expression of the potassium chloride co-transporter 2 (KCC2) at the spinal cord

Abstract: this study demonstrates that the microglial activation at the spinal cord contributes to mechanical hyperalgesia and spinal neuronal hyperactivity induced by diabetes, apparently by regulating the KCC2 expression. These effects do not seem to be mediated by BDNF, which is an important difference from other chronic pain conditions. New targets directed to prevent spinal microglia activation should be considered for the treatment of mechanical hyperalgesia induced by diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
2
45
1
Order By: Relevance
“…Thus, P2X4R‐stimulated microglia release BDNF as a crucial factor to signal to lamina I neurons, causing aberrant nociceptive output that contributes to neuropathic pain (Figure 3)8. Interestingly, a decrease in KCC2 expression in the spinal cord has also been reported in STZ‐induced diabetic rats24. The decrease was suppressed by treatment with minocycline.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, P2X4R‐stimulated microglia release BDNF as a crucial factor to signal to lamina I neurons, causing aberrant nociceptive output that contributes to neuropathic pain (Figure 3)8. Interestingly, a decrease in KCC2 expression in the spinal cord has also been reported in STZ‐induced diabetic rats24. The decrease was suppressed by treatment with minocycline.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 93%
“…The decrease was suppressed by treatment with minocycline. Furthermore, blocking the BDNF action in STZ‐injected rats by tropomyosin‐related kinase B/fragment, crystallizable domain was found to induce moderate effects on mechanical hyperalgesia, although BDNF levels were not increased in STZ‐diabetic rats24. Although P2X4R expression in spinal microglia under diabetic conditions remains unknown, microglial regulation of KCC2 could be a mechanism of diabetes‐induced neuropathic pain.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 95%
“…Mechanisms that have been suggested to contribute to diabetic neuropathic pain include chronic nerve damage (i.e., peripheral neuropathy) due to secondary vascular disease (Beisswenger, 1976;Bays and Pfeifer, 1988), microglial inflammation in the CNS (Tsuda et al, 2008;Pabreja et al, 2011), dysregulation of potassium-chloride cotransporter 2 (KCC2) activity (Morgado et al, 2011), and altered growth factor and sodium channel expression in DRG neurons (Craner et al, 2002a,b). Only a few studies have investigated the possibility of morphological alterations of postsynaptic structures within second-order sensory neurons in diabetes as an underlying mechanism for diabetic neuropathic pain (Yamano et al, 1986;Malone et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ledeboer et al (2005) showed that intrathecal minocycline prevents mechanical allodynia induced by perisciatic administration of zymosan or that induced by spinal immune activation after intrathecal injection of gp120 from human immunodeficiency virus (HIV)-1. Minocycline treatment inhibits mechanical allodynia in streptozotocin-diabetic rats, a model of peripheral diabetic neuropathy (Morgado et al 2011). Basing on evidence of neuroprotective effect induced by minocycline and the association of this effect with inhibition of microglial activation (Yrjanheikki et al 1999), Raghavendra et al (2003) showed that intraperitoneal minocycline prevents the development of mechanical allodynia and thermal hyperalgesia after L5 spinal nerve ligation.…”
Section: Antihypernociceptive Effectsmentioning
confidence: 98%
“…Treatments available to date are based on the empirical use of old unconventional drugs (Dray 2008). In this context, minocycline has been undergoing preclinical studies (Raghavendra et al 2003;Ledeboer et al 2005;Mei et al 2011;Morgado et al 2011). Ledeboer et al (2005) showed that intrathecal minocycline prevents mechanical allodynia induced by perisciatic administration of zymosan or that induced by spinal immune activation after intrathecal injection of gp120 from human immunodeficiency virus (HIV)-1.…”
Section: Antihypernociceptive Effectsmentioning
confidence: 99%